Economic situation of table egg production in Hungary - Szőllősi, László; Molnár, Szilvia (Animal welfare, Ethology and Housing Systems (AWETH), 2018)
Table egg production plays a significant role in the animal sector, as the consumption and production of eggs and egg products are constantly increasing in the world. In contrast, in the last 10-15 years the Hungarian egg sector has shown rapid erosion; stopping this process and turning the trend are recognized as sectoral and national economic interests. The low competitiveness of the sector can be attributed to a number of factors, including efficiency, economies of scale and profitability. The objective of this study is to evaluate the cost and income situation of the Hungarian table egg production in 2013-2017. Model calculation was used to examine the impact of the changes of the main input-output prices and the production parameters on economic indicators.